Peran Kemudahan, Kemanfaatan, Keamanan, dan Kepercayaan dalam Mendorong Adopsi QRIS : Bukti Empiris Dari Pedagang Pasar Tradisional Gawok di Sukoharjo, Jawa Tengah - Amara Indah Ramadhani; Heni Susilowati (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Technological developments in the financial sector are changing people's lifestyles, one of which is a more effective cashless payment system using the Indonesian Standard Quick Response Code (QRIS). The aim of this research is to find the effect of convenience, usefulness, security and trust on the use of Quick Response Code Indonesian Standard (QRIS) barcodes at the Gawok Traditional Market. The total population of 35 respondents from Gawok Traditional Market traders was sampled using a total sampling technique. The method in this research is multiple linear regression analysis method with quantitative research. The results provide the conclusion that the variables of convenience, usefulness, security and trust have a significant and influential effect on the decision to use Quick Response Code Indonesian Standard (QRIS) barcodes in Gawok Traditional Market shophouses so that these four variables greatly influence the decision to use Quick Response Code Indonesian Standard (QRIS) barcodes in Gawok Traditional Market Shophouse. This study recommends improving security and building trust through transparency and education for traders. Enhancing ease of use and increasing QRIS benefits, such as usage incentives, are also essential. The practical implication is that QRIS implementation in traditional markets will be more effective if supported by technical assistance and improved positive perceptions of its security and usefulness.